Strategi Pemasaran World of Mouth dan Online Dalam Sentra Industri Rumah Abon Ikan Lele di Jiwan Kabupaten Madiun - Dian Citaningtyas Ari Kadi; Rizal Ula Ananta Fauzi; Bima Budi Cahyana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Micro, Small and Medium Enterprises (MSMEs) we choose to be engaged in the center of making catfish floss, which is located in Madiun Regency, more precisely in Jiwan. This processed product made from catfish is still not in high demand because people still don't know or know it. The community still believes in processed products from other basic ingredients, such as shredded chicken and shredded beef. In fact, when compared to the taste, shredded catfish is not much different from shredded from other basic ingredients. And in terms of price, the catfish floss is much cheaper or more affordable than the others. Therefore, our group will propose and help this business in terms of marketing so that it is better known by the public. We will carry out more intensive promotions, besides through word of mouth, we will also apply online marketing strategies through social media.